The Impact of Emotional Intelligence towards Political Behaviour among University Students - Sarawati Johar, Siti; Sanif, Sazuliana; Ani, Fauziah; Halim, Harliana; Hamzah, Shahidah; Zainatul Nadra Zainol, Nur; Farhana Saparudin, Intan; Nazliah Salih, Adibah; Zirwatul Aida Raja Ibrahim, Raja; Aisyah Panatik Abdul Rahman, Siti (International Journal of Engineering and Technology, 2018)
In this experimental study, the issue is focused on the influence of emotional intelligence in shaping the political behaviour of university youth students. The specific objective of this study is to examine the impacts of emotional intelligence competency on political behaviour among youth at the university by looking at the significance difference in the treatment group and the control group through application of emotional intelligence module. A total of 608 university students were selected as respondents from four public universities in Malaysia. The measuring tools used were the Emotional Intelligence Self-Description Inventory (EISDI), and the Political Behaviour Questionnaire (PBQ). In this study, T-test analysis and ANOVA test were used to determine the difference between the two control and treatment groups. The findings showed that there was a significant impact on the post-test for the treatment group due to the pre-and post-treatment differences. However, the findings from the control group showed no significant value. In addition, the findings show that the treatment group has the impact of changing the political behaviour with the implementation of emotional intelligence competencies in the teaching modules. The findings of this study provided sharing of the importance of the implementation of emotional intelligence among university students to form positive behaviours in political aspects.Â